Adenosine receptor signalling: Probing the potential pathways for the ministration of neuropathic pain - Shaw S.; Uniyal A.; Gadepalli A.; Tiwari V.; Belinskaia D.A.; Shestakova N.N.; Venugopala K.N.; Deb P.K.; Tiwari V. (My University, 2025)
Neuropathic pain is a critical burdensome problem due to the complex interplay of several pathological mechanisms and lack of availability of effective therapeutic interventions. The available therapeutic options are associated with a variety of limitations, including severe side effects, and unmet medical needs, warranting further research to identify and validate potential targets. Adenosine receptors system is a widely studied target, which evidently was successful in alleviation of neuropathic pain in several experimental paradigms, and researchers are putting efforts in building its clinical roadmap. The adenosine receptors act by different mechanisms and targeting adenosine receptors for neuropathic pain includes several important pathways such as p38-mitogen-activated protein kinases (MAPK), extracellular signal-regulated kinases (ERK), brain-derived neurotrophic factor (BDNF) signalling, γ-aminobutyric acid (GABA) as well as the ion channel modulations. Various studies have also shown the relevance of targeting adenosine receptors in chemotherapy-induced neuropathic pain and diabetic neuropathy. Several drugs acting on adenosine receptors have undergone clinical trials for management of neuropathic pain, whereas many other drugs are yet to be studied to find a potential anti-nociceptive agent. In this review, we have discussed the roadmap of adenosine receptors as a potential target for the treatment of neuropathic pain. © 2020 Elsevier B.V.